Persistent fifth aortic arch: a comprehensive literature review - Shan, Haiyan; Du, Xiaolan; Zheng, Guangrong; Ke, Tengfei; Liao, Chengde; Yang, Haiyan (Frontiers in Pediatrics, 2023)
Persistent fifth aortic arch (PFAA) is an extremely rare congenital cardiovascular anomaly resulting from the failure of the fifth aortic arch to degenerate during embryonic development; it is often associated with various other cardiovascular anomalies. Despite being first reported by Van Praagh in 1969, there have been only a few individual case reports. Owing to its rarity and lack of comprehensive understanding, PFAA is often misdiagnosed or missed diagnosed during clinical. Thus, this review aimed to summarise the embryonic development, pathological classification, imaging diagnosis, and clinical treatment of PFAA to improve its overall understanding, ultimately helping in accurate diagnosis and treatment.